USE OF ICT BY SCHOOL ADMINISTRATORS IN COMBATING CYBERCRIME IN NIGERIAN UNIVERSITIES (Scientific Journal of Educational Management, Research and law, 2025)
Over the years, the revolutionary advancements in Information and Communication Technology (ICT) have undeniably brought forth significant and noteworthy transformations to the landscape of academic practice. These transformations have predominantly been witnessed in the realms of teaching and learning, research, and university administration, thereby shaping the very essence of educational institutions. However, amidst these ground-breaking progressions, it is disconcerting to observe that cybercrime has emerged as a prevalent and pressing concern within the educational sphere. Regrettably, Nigerian universities have experienced a distressing upsurge in cybercrime incidents, demanding an urgent call to address this escalating issue. Cybercrime encompasses a broad range of criminal activities facilitated through digital technology, targeting individuals, organizations, and governments alike. It includes unauthorized access to computer systems, data theft, online fraud, identity theft, and cyberbullying, etc. The integration of Information and Communication Technology (ICT) in the administration of Nigerian universities has become increasingly pivotal in addressing the growing challenge of cybercrime. This study explores the proactive measures taken by school administrators to combat cyber threats through the effective use of ICT tools and strategies. The research highlights the types of cybercrimes prevalent in Nigerian higher education institutions, including data breaches, phishing attacks, and identity theft. It examines the role of ICT in enhancing security protocols, promoting digital literacy among staff and students, and implementing comprehensive cybersecurity policies. Through a combination of qualitative and quantitative methods, the study evaluates the effectiveness of these measures and identifies best practices.